Analisis Tingkat Kecacatan Produk Lever Assy Parking Brake Menggunakan Metode Statistical Quality Control (SQC) - Rianita Puspa Sari; Dewi Puspita (JIEMS (Journal of Industrial Engineering and Management Systems), 2018)
The company always tries to meet customer demands, so it must be able to provide good product quality. Quality control is always carried out by manufacturing companies for the creation of zero defects. Lever Assy Parking Brake is part of the cars spare parts produced by manufacturing company X and must have a zero defect product quality level. The purpose of this study was to determine the level of product defect using the Statistical Quality Control (SQC) method. Data was carried out with process control procedures. This study showed that the product defect rate of Lever Assy Parking Brake with Statistical Quality Control (SQC) method in March 2018 was very large. As seen from the 22 data production processes, 13 production process data (59 percent) were out-of-control but still fell within the specification limit of 9 ± 0.5 mm. Meanwhile, only 9 data production processes (41 percent) were in control. So there is a need to analyze causes and corrective actions. R control chart shows the process that has been stable or under control has a UCL (Upper Control Limit) value of 0.21, the LCL (Lower Control Limit) value of 0 and a value of CL (central line) of 0.10. Whereas ????̅ chart shows the control limit with UCL value of 9.39, LCL value is 9.27 and CL value is 9.33.